The Role of PCNA Posttranslational Modifications in Translesion Synthesis - Montaser Shaheen; Ilanchezhian Shanmugam; Robert Hromas (Journal of Nucleic Acids)
Organisms are predisposed to different types in DNA damage. Multiple mechanisms have evolved to deal with the individual DNA lesions. Translesion synthesis is a special pathway that enables the replication fork to bypass blocking lesions. Proliferative Cell Nuclear Antigen (PCNA), which is an essential component of the fork, undergoes posttranslational modifications, particularly ubiquitylation and sumoylation that are critical for lesion bypass and for filling of DNA gaps which result from this bypass. A special ubiquitylation system, represented by the Rad6 group of ubiquitin conjugating and ligating enzymes, mediates PCNA mono- and polyubiquitylation in response to fork stalling. The E2 SUMO conjugating enzyme Ubc9 and the E3 SUMO ligase Siz1 are responsible for PCNA sumoylation during undisturbed S phase and in response to fork stalling as well. PCNA monoubiquitylation mediated by Rad6/Rad18 recruits special polymerases to bypass the lesion and fill in the DNA gaps. PCNA polyubiquitylation achieved by ubc13-mms2/Rad 5 in yeast mediates an error-free pathway of lesion bypass likely through template switch. PCNA sumoylation appears required for this error-free pathway, and it plays an antirecombinational role during normal replication by recruiting the helicase Srs2 to prevent sister chromatid exchange and hyper-recombination.